Effect of egg avoidance diet by nursing mothers on the incidence of atopic dermatitis in infants - Neti Nurani; Endy Paryanto Prawirohartono; A. Samik Wahab (Paediatrica Indonesiana, 2008)
Background The prevalence of allergic and atopic diseases hasincreased rapidly and remains a social as well as an economicproblem for the patients on account of its chronic nature. In orderto decrease the atopic diseases, especially atopic dermatitis ininfants, nursing mothers should avoid allergenic foods as apreventive sensitization. Egg allergy is the most common cause offood allergy, and is closely related to atopic dermatitis in children.Objective To determine whether egg avoidance diet by nursingmothers could decrease the incidence of atopic dermatitis ininfants.Method We conducted a parallel randomized-controlled trial.Seventy-nine subjects eligible for the study were divided into twogroups: egg avoidance and non-egg avoidance group. Blockrandomization is used for random allocation. Intervention startedsince mothers had had delivery until their children were 4 monthsold. The primary outcomes were clinical atopic dermatitis.Result Atopic dermatitis incidence in maternal egg avoidancegroup was significantly lower than non-avoidance group. Non-avoidance, family history of asthma, and maternal allergy are thefactors significantly influencing atopic dermatitis incidence (OR6.17; OR 4.73; OR 0.14), respectively.Conclusion Egg avoidance by nursing mothers could decrease theincidence of atopic dermatitis in infants. Non-egg avoidance andasthma in the families are factors significantly inducing the incidenceof atopic dermatitis.